1963
DOI: 10.1029/jz068i010p03328
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescent techniques for studying nighttime winds in the upper atmosphere

Abstract: For the study of large‐scale mass‐transport processes (wind speed, direction, and shear, diffusion and turbulence), rocket‐released smoke trails have been used for altitudes below 80 km, and the twilight sodium trail has been used for higher altitudes [Manring et al., 1962]. However, the latter is restricted to a 20‐ to 40‐minute period at sunset and sunrise, when the cloud is sunlit and the sky background is dark. Two different types of payload for generating persistent, glowing trails under full night condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The technique, which has been in use for nearly 15 years, consists of observing the vapour release at twilight by means of resonant scattering of the incident solar radiation against a dark sky foreground (Manring et al 1959) or at night by means of a chemiluminescent reaction between the chemical tracer and the ambient atmosphere (Rosenberg and Golomb 1963). The confinement of the observation period to less than half of the day has meant that study of the propagation of tides in the atmosphere is necessarily incomplete (Murphy and Bull 1968).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique, which has been in use for nearly 15 years, consists of observing the vapour release at twilight by means of resonant scattering of the incident solar radiation against a dark sky foreground (Manring et al 1959) or at night by means of a chemiluminescent reaction between the chemical tracer and the ambient atmosphere (Rosenberg and Golomb 1963). The confinement of the observation period to less than half of the day has meant that study of the propagation of tides in the atmosphere is necessarily incomplete (Murphy and Bull 1968).…”
Section: Introductionmentioning
confidence: 99%
“…The confinement of the observation period to less than half of the day has meant that study of the propagation of tides in the atmosphere is necessarily incomplete (Murphy and Bull 1968). Alternatively bold assumptions must be made to determine the magnitude of these tides (Woodrum and Justus 1968).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the earliest active experiments, metallic sodium vapor was injected into the upper atmosphere from 50 km to 130 km at twilight on both 21 January and 12 October 1955, as a tracer for neutral wind sounding. Afterward, a notable campaign, Project Firefly, was conducted by the Air Force Cambridge Research Laboratory in 1960s [ Rosenberg , ; Rosenberg and Golomb , ; Rosenberg et al , , ], with the intention of investigating the effect of some different kinds of chemicals released. Since then, a mass of chemical releases have been performed, such as the Active Magnetospheric Particle Tracer Explorers (AMPTE) operation [ Gurnett et al , ; Bernhardt et al , ], the Brazilian Ionospheric Modification Experiment [ Klobuchar and Abdu , ], the Combined Release and Radiation Effects Satellite (CRRES) experiments [ Huba et al , ; Bernhardt et al , ; Wescott et al , ], the space shuttle orbital maneuver subsystem engines [ Bernhardt et al , ], and the Charged Aerosol Release Experiments [ Bernhardt et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…In reaction to the initial suggestion by Bates [1950] that the upper atmosphere could be studied by the ejection of specific chemicals from rockets, extensive investigations were made of atmospheric winds, temperatures, densities, and deactivation and excitation phenomena by the release of various molecular species in the high sunlit atmosphere at twilight. During the last fifteen years, atmospheric spectra due to the oxides of aluminum and barium have been studied by several investigators [Armstrong, 1963;Authier, 1964;Authier et al, 1964;Rosenberg et al, 1963aRosenberg et al, , b, 1964Johnson, 1965;Golomb and MacLeod, 1966;Golomb et al, 1967Golomb et al, , 1968Low, 1967;Harang, 1968Harang, , 1970Harang and $toffregen, 1969;Rees, 1968Rees, , 1971Simon, 1971; Degen et al, and are yet to be identified either in the atmosphere or in the laboratory. It appears that these infrared bands may be of some ionospheric significance and warrant further search in the upper atmosphere.…”
mentioning
confidence: 99%